Sharia-Based Economic Development as a Solution to Poverty Reduction in Jember Regency - Fauzan; Nur Ika Mauliyah (Research Horizon, 2025)
Poverty in Jember Regency remains a serious issue, with many people lacking access to resources and economic opportunities. Based on principles of justice and ethical financing, sharia economics offers a promising solution to address this challenge. This study aims to analyze the potential and challenges of sharia-based economic institutions in reducing poverty in Jember Regency. Using a descriptive qualitative approach, the research explored sharia economic models, such as Islamic microfinance institutions, sharia cooperatives, and productive zakat programs, through interviews with 18 informants, observations, and document analysis. The findings show that these institutions empower poor communities by providing microfinance, supporting small businesses, and promoting fair wealth distribution. However, low financial literacy, weak institutional systems, and limited government coordination hinder their effectiveness. The study concludes that strengthening sharia institutions, improving community education, and enhancing collaboration with local government can make sharia economics a sustainable tool for poverty alleviation. Islamic boarding schools, with their strong community ties, play a key role in this process but need better funding and digital tools to expand their impact.